Effects of maternal overnutrition and metabolic challenge in adult life on the histological integrity of the liver and intestinal epithelium in rabbits - Cano, Lucía Carolina; Navarrete, Erika; Medina, Pedro; Ochoa-Romo, Juan Pablo; Díaz, Georgina; Montúfar-Chaveznava, Rodrigo; Vigueras-Villaseñor, Rosa María; Caldelas, Ivette (Frontiers in Nutrition, 2025)
IntroductionMaternal overnutrition during critical stages of embryonic development has been implicated as a major determinant of developmental and metabolic disturbances in offspring. Current data concerning how perinatal exposure to high-fat and high-carbohydrate diets, followed by re-exposure in adulthood (metabolic challenge), affects the metabolic regulation and structural integrity of the liver and small intestine, key organs of the gut–liver axis (GLA), are limited.MethodsFemale rabbits were fed either a standard diet (SD) or a high-fat and high-carbohydrate diet (HFCD) before mating and during gestation. The offspring on postnatal day 440 were challenged with an HFCD or SD for 30 days and assigned to the following groups: SD–SD (obtained from does fed SD and challenged with SD), SD–HFCD, HFCD–SD, and HFCD–HFCD. After completion of the metabolic challenge, glucose, total cholesterol, low- and high-density lipoproteins, free fatty acids, triglycerides, gamma-glutamyl transferase, bilirubin, aminotransferases, and the level of lipopolysaccharides (LPS) were measured. Additionally, histological analysis of the liver and duodenum was conducted using several staining methods.ResultsAt both metabolic and histopathological levels, rabbits exposed to HFCD during adulthood exhibited more pronounced alterations. In particular, the HFCD–HFCD group showed the greatest degree of impairment. Moreover, morphological changes were notably more severe in the duodenal tissue than in the liver tissue.DiscussionThese results indicate that exposure to an HFCD during critical developmental windows—both gestation and adulthood—induces significant metabolic disturbances and histological damage in the liver and intestinal epithelium. These effects appear to depend on the timing and duration of dietary exposure.